Perceived Barriers to Accessing Tuberculosis Care Among Multidrug Resistant Tuberculosis (MDR-TB) Patients: A Qualitative Study in Indonesia - Nimah, Lailatun; Tristiana, Rr Dian; Hidayati, Laily; Kusmiati, Tutik; Sulistyono, R Endro (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia has one of the highest MDR-TB burdens in the world. The success rate of MDR-TB treatment in Indonesia is still low. Indonesia changed the health system policy, which is called the National Health Insurance, in 2013. The purpose of this study is to provide a description from the point of view of MDR-TB patients about barriers during their treatment, although the health system in Indonesia has changed. This study used qualitative semi- structured in-depth questions. Fifteen MDR-TB patients were interviewed concerning the barriers during their treatment. Purposive sampling was used to recruit study participants. Thematic analysis was used to identify and analyse the main topics. Topics generated were financial barriers, poor service, inadequate hospital facilities, ineffective communication of patient-provider, stigma, and lack of social support. Each theme was from verbatim transcripts defined during the coding process. Codes and themes were developed to coincide with data collection. Periodic monitoring of aid disbursements, improvement of hospital services including health workers and facilities, increased social support, increased knowledge and home-based MDR-TB service programs can be implemented to reduce the perceived barriers for MDR-TB patients during treatment.